Dynamic Characteristics of Signatures: Effects of Writer Style on Genuine and Simulated Signatures1. Issue 1 (24th November 2014) - Mohammed, Linton; Found, Bryan; Caligiuri, Michael; Rogers, Doug
Abstract The aims of this study were to determine if computer‐measured dynamic features (duration, size, velocity, jerk, and pen pressure) differ between genuine and simulated signatures. Sixty subjects (3 equal groups of 3 signature styles) each provided 10 naturally written (genuine) signatures. Each of these subjects then provided 15 simulations of each of three model signatures. The genuine (N = 600) and simulated (N = 2700) signatures were collected using a digitizing tablet. MovAlyzeR® software was used to estimate kinematic parameters for each pen stroke. Stroke duration, velocity, and pen pressure were found to discriminate between genuine and simulated signatures regardless of the simulator's own style of signature or the style of signature being simulated. However, there was a significant interaction between style and condition for size and jerk (a measure of smoothness). The results of this study, based on quantitative analysis and dynamic handwriting features, indicate that the style of the simulator's own signature and the style of signature being simulated can impact the characteristics of handwriting movements for simulations. Writer style characteristics might therefore need to be taken into consideration as potentially significant when evaluating signature features with a view to forming opinions regarding authenticity.